2017 Cardiovascular and Stroke Endpoint Definitions for Clinical Trials - Hicks, Karen A; Mahaffey, Kenneth W; Mehran, Roxana; Nissen, Steven E; Wiviott, Stephen D; Dunn, Billy; Solomon, Scott D; Marler, John R; Teerlink, John R; Farb, Andrew; Morrow, David A; Targum, Shari L; et al. (Circulation (New York, N.Y.), 2018)
This publication describes uniform definitions for cardiovascular and stroke outcomes developed by the Standardized Data Collection for Cardiovascular Trials Initiative and the US Food and Drug Administration (FDA). The FDA established the Standardized Data Collection for Cardiovascular Trials Initiative in 2009 to simplify the design and conduct of clinical trials intended to support marketing applications. The writing committee recognizes that these definitions may be used in other types of clinical trials and clinical care processes where appropriate. Use of these definitions at the FDA has enhanced the ability to aggregate data within and across medical product development programs, conduct meta-analyses to evaluate cardiovascular safety, integrate data from multiple trials, and compare effectiveness of drugs and devices. Further study is needed to determine whether prospective data collection using these common definitions improves the design, conduct, and interpretability of the results of clinical trials.